2013
DOI: 10.1099/mic.0.067678-0
|View full text |Cite
|
Sign up to set email alerts
|

Compound(s) secreted by Lactobacillus casei strain Shirota YIT9029 irreversibly and reversibly impair the swimming motility of Helicobacter pylori and Salmonella enterica serovar Typhimurium, respectively

Abstract: We conducted experiments in order to examine whether the probiotic Lactobacillus casei strain Shirota YIT9029 (LcS) in vitro and in vivo antagonism of Helicobacter pylori and Salmonella, involves inhibition of the swimming motility of these pathogens. We report the irreversible inhibition of the swimming motility of H. pylori strain 1101 and reversible inhibition of Salmonella enterica serovar Typhimurium (S. Typhimurium) strain SL1344 by compound(s) secreted by LcS. In H. pylori 1101, irreversible inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…The transformation of H. pylori from culturable spiral forms into non-culturable coccoids occurs during exposition to adverse conditions, including: nutrient starvation [ 19 , 20 ], prolonged in vitro incubation [ 21 , 22 ], presence of low or high temperature [ 21 , 23 , 24 ], incubation at alkaline pH [ 25 ], drastic change of culture environment from a nutrient-rich medium to pure water [ 26 , 27 ], incubation in the deficiency/absence of CO 2 [ 28 , 29 ], or exposure to antimicrobial compounds, e.g. antibiotics [ 30 , 31 ], proton pump inhibitors (PPIs) [ 22 , 32 ], and compounds secreted by bacteria of the genus Lactobacillus [ 33 , 34 ] and Streptococcus [ 35 ] ( Figure 1 ). Although coccoid forms are often observed during laboratory work with H. pylori , the presence of these forms has been reported in many in vivo cases [ 36 – 38 ].…”
Section: Coccoid Formsmentioning
confidence: 99%
“…The transformation of H. pylori from culturable spiral forms into non-culturable coccoids occurs during exposition to adverse conditions, including: nutrient starvation [ 19 , 20 ], prolonged in vitro incubation [ 21 , 22 ], presence of low or high temperature [ 21 , 23 , 24 ], incubation at alkaline pH [ 25 ], drastic change of culture environment from a nutrient-rich medium to pure water [ 26 , 27 ], incubation in the deficiency/absence of CO 2 [ 28 , 29 ], or exposure to antimicrobial compounds, e.g. antibiotics [ 30 , 31 ], proton pump inhibitors (PPIs) [ 22 , 32 ], and compounds secreted by bacteria of the genus Lactobacillus [ 33 , 34 ] and Streptococcus [ 35 ] ( Figure 1 ). Although coccoid forms are often observed during laboratory work with H. pylori , the presence of these forms has been reported in many in vivo cases [ 36 – 38 ].…”
Section: Coccoid Formsmentioning
confidence: 99%
“…Impairment of S. Typhimurium swimming motility has been observed after treatment with CFCSs of L. acidophilus LB and L. casei Shirota as a result of membrane depolarization that affects the functionality of the flagellar motor but not flagellum expression (147,148). The inhibition of the swimming motility results from the secretion of a small compound(s) (dialysis cutoff, 1,000 Da), which in the case of the L. acidophilus LB compound(s) was heat and trypsin resistant whereas in that of the L. casei Shirota compound(s) was heat and trypsin sensitive (147,148).…”
Section: Direct Activities Against Enterovirulent Bacteriamentioning
confidence: 99%
“…In a study on the antagonistic effect of L. casei on H. pylori and salmonella, it was revealed that L. casei inhibited the expression of H. pylori flagellin genes A and B, which ultimately prevented from bacterial movement and resulted in morphology change to coccoid form (22). In the present study, most lactobacilli isolated from the milk of dromedary were related to L. plantarum, L. fermentum and L. casei.…”
Section: / Sikarchi and Fozounimentioning
confidence: 78%